Implementasi Model Project Based Learning untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi dalam IPS Kelas V Sekolah Dasar - Hana Nur Fadillah; Takiddin Takiddin (Elementar : Jurnal Pendidikan Dasar, 2022)
This research was conducted with the aim of knowing the implementation of the project based learning model to improve students' higher-order thinking skills in social science material in social sciences. The method used in this study is a qualitative survey method with a total of 22 students. The instruments used in this research are observation and documentation. The data analysis used is qualitative data analysis. Qualitative data analysis is used to provide information that describes the improvement in the results of teacher performance and student activities by using a project_based learning model that is applied during the implementation of learning by using observation sheets. This shows that from the first meeting to the end of four meetings the teacher's performance from 70% to 100% and student activity from 60% to 100%. The conclusion in this study is that students' high-level thinking in social studies can be improved by implementing a project based learning model for class VB students at SDN.